Academic Writing for International Students of Business - Dutkiewicz, Keri (Journal of International Students, 2016)
The recently released 2nd edition of Stephen Bailey’s Academic Writing for International Students of Business (2015) overviews general concepts about academic writing in English for non-native speakers studying business. Bailey’s text can be utilized both as a classroom text and as a self-study guide, supported by a corresponding answer key at the end of the text. The 2nd edition differs from the first in that it offers a new section on writing a literature review (replacing the composing a CV section in the previous edition) and a more in-depth explanation on the correct use of definite articles in English. Like the first edition, the 2nd edition is available as a softbound book as well as an electronic text in an easy to utilize, downloadable format